1998
DOI: 10.1002/pen.10375
|View full text |Cite
|
Sign up to set email alerts
|

Compressive behavior of microcellular polystyrene foams processed in supercritical carbon dioxide

Abstract: Microcellular polystyrene foams have been prepared using supercritical carbon dioxide as the foaming agent. The cellular structures resulting from this process have been shown to have a significant effect on the corresponding mechanical properties of the foams. Compression tests were performed on highly expanded foams having oriented, anisotropic cells. For these materials an anisotropic foam model can be used to predict the effect of cell size and shape on the compressive yield stress. Beyond yield, the foams… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(68 citation statements)
references
References 15 publications
2
66
0
Order By: Relevance
“…Foaming temperature and foaming time are the key parameters to adjust the cellular structure of the final product. 13,14 Using this process, microcellular polymers, such as polystyrene, 15 polypropylene, 16,17 polyethersulfone and polyphenylsulfone, 18,19 polycarbonate, 20 Poly (methyl methacrylate) 21 and biodegradable poly (lactic acid) have been prepared. 22 In all the cases, one of the main objectives is reducing material bulk density, reducing cell size and/or increasing the cell number density of the cellular polymer produced.…”
Section: Introductionmentioning
confidence: 99%
“…Foaming temperature and foaming time are the key parameters to adjust the cellular structure of the final product. 13,14 Using this process, microcellular polymers, such as polystyrene, 15 polypropylene, 16,17 polyethersulfone and polyphenylsulfone, 18,19 polycarbonate, 20 Poly (methyl methacrylate) 21 and biodegradable poly (lactic acid) have been prepared. 22 In all the cases, one of the main objectives is reducing material bulk density, reducing cell size and/or increasing the cell number density of the cellular polymer produced.…”
Section: Introductionmentioning
confidence: 99%
“…Youn and Suh [16] found that the flexural toughness of polyester microcellular foam increases by a factor of 3 for 30% bubble volume fraction compared to the neat polyester, although the strength is about the same. Aroka [17] investigated the effect of the cell size and shape on the compressive yield stress of microcellular PS foam, and found that the compressive strength of foam increases with the increase of cell size, and their data are higher than those predicted by an anisotropic foam model. Recently there has been some research dealing with the effect of relative density on the mechanical property of microcellular composite foams [18,19], however, they only related mechanical property with the relative density, but fewer reports are available on the effect of processing parameters and cell size on the tensile property.…”
Section: Introductionmentioning
confidence: 90%
“…The interconnection and geometry of pores, which depend on the tissue to regenerate, physicochemical properties and mechanical resistance of the material, play in these biomedical applications a major role. Thus, there are several methods to produce scaffolds, which include gas foaming [100], sintering fiber meshes [101], solvent casting [102], polymerization in solution [80,103], porogen technique [104,105], freeze-drying techniques [106,107], electrospinning [108], 3D printing [109], 3D bioplotting of scaffold with cells [110], etc. For example, acrylic scaffolds with interconnected spherical pores and controlled hydrophilicity with interconnected porous structure were synthesized using a template of sintered PMMA microspheres of controlled size.…”
Section: Porosity In Scaffolds For Tissue Engineeringmentioning
confidence: 99%